Prediction of Waste Generation in Yogyakarta Special Region Province Using ARIMA Model - Nur Azizah, Resti; Aji, Ranggi Praharaningtyas (International Journal of Informatics and Information Systems, 2024)
Waste is a problem in big cities in Indonesia, including in the Special Region of Yogyakarta which has a high population. In addition, the large tourism potential triggers waste problems that are often experienced by the Special Region of Yogyakarta. The average increase in waste reaches 11.53% per year. This causes an imbalance in the ability to manage the waste system in the province. To overcome this, an analysis is needed to project waste generation to support waste management strategies and processes. This research uses the CRISP-DM framework to facilitate the stages of analysis and effective and efficient decision making. The data used is a time series of waste generation per year in tons from districts or cities from 2016 to 2022. The model used to make predictions is the ARIMA model. This model was chosen because it is suitable for time series analysis and is the most commonly used model. The result of this prediction is that the projected waste generation from 2023 to 2025 in each district or city in the Special Region of Yogyakarta has increased significantly. Based on the ARIMA model, it is projected that the average waste generation of DIY Province will increase from a total of 638 thousand tons in 2022 to 642 thousand tons in 2023, and is expected to continue to increase by 5-7 thousand tons per year.